Factors Affecting the Conversion of Rubber Land to Oil Palm in Benteng Hulu Village Mempura District Siak Regency - Wijaya, Alwa; Maharani, Evy; Arifudin, Arifudin (Universitas Jambi, 2023)
Farmers convert land from rubber to oil palm in order to increase their revenue. The purpose of this study is to identify the factors that influence rubber land conversion to oil palm in Benteng Hulu Village, Mempura District, Siak Regency. The sampling approach employed was simple random sampling, with 60 sample farmers, 30 of whom converted land and 30 of whom did not convert land to oil palm. Descriptive analysis and logistic regression were employed in the analysis. According to the findings of the study, farmers' ages are still in the productive range, their land area is typically 0.1-3.5 ha, The bulk of their education is at the high school/equivalent level, they have more than 10 years of agricultural experience, and the maximum number of dependents a farmer has is 0-2 individuals. The model feasibility test results show that there is no discrepancy between the two estimates of the logistic regression model and the observation data, indicating that the model is feasible and appropriate for usage. The Omnibus test of model coefficients was performed to ensure that the independent variables are FIT with the model, which means that they have a real influence on the model when combined. The R square value indicates a 51.2 percent chance that the independent variable influences the dependent variable. The Wald test reveals that the factors of rubber production and oil palm farming revenue have a minor impact on land conversion.